AVALIAÇÃO FÍSICA DO SOLO EM NASCENTE RECUPERADA NO MUNICÍPIO DE MUNDO NOVO, MS - LINGNAU, Bruno Ian; OZORIO, Jefferson Matheus de Barros; CUNHA, Vinicius Estigarribia; ROSSET, Jean Sergio; CASTILHO, Selene Cristina de Pierri (ANAIS DO ENIC, 2025)
-